KONSEP ALIH WAHANA CERPEN KE NASKAH DRAMA: KAJIAN PUSTAKA - JH. Fahrizal Nur Rizky; Merlinda Putri A; Mabrurotul Umami; Zaimatussa’diyah; Moh. Fikri Zulfikar (Jurnal PENEROKA, 2024)
This research aims to explore the process of converting a short story into a drama script and to understand the elements involved in this process. The scope of the study includes the concept of transfer, structural comparisons between short stories and drama scripts, transfer strategies, dialogue in stories, and elements of dramatization in drama scripts. The research method used is a literature study by collecting data from various sources such as books, scientific journals, articles, and existing research. Analysis was carried out using content and descriptive analysis to understand related theories and the results of previous research. This research data model leads to an in-depth understanding of the creative process of changing a short story into a drama script, focusing on the concept of transfer, structure comparison, transfer strategy, dialogue in the story, and elements of dramatization. Thus, it is hoped that the findings from this research will provide better insight into how literary works in the form of short stories can be adapted into drama scripts more effectively and interestingly. These findings can contribute to the development of knowledge surrounding literature and media transfer and be an important reference for researchers and practitioners in literature and theater.